2004
DOI: 10.1161/01.cir.0000130917.12959.04
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenoceptor Blocker Carvedilol Provides Cardioprotection via an Adenosine-Dependent Mechanism in Ischemic Canine Hearts

Abstract: Background-Carvedilol is a ␤-adrenoceptor blocker with a vasodilatory action that is more effective for the treatment of congestive heart failure than other ␤-blockers. Recently, carvedilol has been reported to reduce oxidative stress, which may consequently reduce the deactivation of adenosine-producing enzymes and increase cardiac adenosine levels. Therefore, carvedilol may also have a protective effect on ischemia and reperfusion injury, because adenosine mediates cardioprotection in ischemic hearts. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 25 publications
2
31
0
1
Order By: Relevance
“…Asanuma et al reported that carvedilol suppressed the frequency of ventricular fibrillation and death through reducing infarct size after ischemia reperfusion injury. 26 This report supports our results that the number of patients died from ACS was lower in the carvedilol group than that in the bisoprolol group. Thus, the dosages of the 2 β-blockers in our study could be sufficient to improve HF.…”
Section: Konishi M Et Alsupporting
confidence: 91%
“…Asanuma et al reported that carvedilol suppressed the frequency of ventricular fibrillation and death through reducing infarct size after ischemia reperfusion injury. 26 This report supports our results that the number of patients died from ACS was lower in the carvedilol group than that in the bisoprolol group. Thus, the dosages of the 2 β-blockers in our study could be sufficient to improve HF.…”
Section: Konishi M Et Alsupporting
confidence: 91%
“…Indeed, many reports show that the blockade of the ␤-adrenoceptor will protect the myocardium from prolonged ischemia-reperfusion. However, possible pharmacological mechanisms other than hemodynamic benefits are under discussion (9,180,238).…”
mentioning
confidence: 99%
“…The actions of beta-blocker were different in the lipophilicity, cardioselectivity, and vasodilatation. Drugs, such as carvedilol, metoprolol and labetalol are lipid solubility and have peripheral vasodilators effects; other drugs, such atenolol and practolol are not lipid solubility and not have peripheral vasodilator effects, moreover possess cardiac selectivity 10,28,29 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Atenolol, a beta-1-selective blocker, is implicating with cross-talk between adrenoceptors and adenosine receptors to promote cardioprotection and other cytoprotective effects 29 . Campos et al 30 where AT attenuated the motor and neural dysfunctions in rat small bowel caused by ischemia-reperfusion.…”
Section: ■ Discussionmentioning
confidence: 99%